Internal police. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows Japanese police unit at Portland, Oregon Assembly Center. Police unit members are all wearing, arm bands with the initials "PD" to denote their status. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.